STUDY OF CORAL REEF DISTRIBUTION AROUND BADUNG STRAIT USING ALOS SATELLITE DATA - -, Suciati; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Coral reef ecosystem has become a centre of interest because of the development of marine tourism development,coral fragment trade, and other activities that are able to destroy coral reef ecosystem. ALOS with AVNIR-2 sensor wasselected because it has 3 visible spectrums which have the ability of penetration into water column, also it have highenough of spatial resolution i.e.10 meters.The aims of this research are: 1) to identify the level of accuracy of ALOS satellite image in activity for coral reefdistribution mapping and 2) to identify the general condition of coral reefs in around Badung Strait.Preliminary processes of image processing are geometric correction and atmosphere correction. Water columneffect was reduced by Lyzenga Algorithm. Five classes were determined by multispectral classification process e.i. coral,vegetation, sand, rubble of coral and substrate. Ground check was done to identify the accuracy level. The methodaccuracy by Lillesand and Kiefer was used in this research.The result of accuracy test shows that classification accuracy was 87.16% for overall accuracy. Results of imageinterpretation show that live coral in around Badung strait is estimated to have about 141,056 hectares width. It wascovering Denpasar Regency in the east and south-east side of Serangan Island with the fringing reef type; KlungkungRegency in the west side of Lembongan Island with the fringing reef type and in the south side with the platform type,while in Gianyar Regency was not found the coral reef distribution.
Keywords: Coral reef distribution, ALOS satellite image